Cultivating Integrity through Ethnopedagogy: The Implementation of Cublak Suweng Traditional Game in Early Childhood Education - Suharti Suharti; Mallevi Agustin Ningrum; Salwa Rohmania Al Fakhri; Dhian Gowinda Luh Safitri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Instilling integrity in early childhood is often hindered by cognitive limitations in understanding abstract concepts and psychological barriers such as the fear of negative consequences. This study aims to analyze the effectiveness of implementing ethnopedagogy through the traditional game Cublak Suweng in fostering honesty among children aged 5–6 years. Using a qualitative approach with a case study design, this research involved seven children in an Islamic-based kindergarten. Data were collected through participatory observation, interviews, and documentation across four intervention sessions. Data were analyzed using thematic analysis techniques, encompassing data reduction, data display, and conclusion drawing. The results indicate that the mechanics of the Cublak Suweng game successfully deconstruct children's emotional barriers by creating a safe space when making mistakes. Furthermore, democratic social interaction within the game encourages a transition in children's morality from the heteronomous phase toward autonomous consciousness. The study concludes that ethnopedagogy based on local wisdom is more effective than conventional lecture methods in internalizing honesty values spontaneously; therefore, early childhood educators are encouraged to integrate traditional games into character education curricula as a contextual and affective learning method.